2019
DOI: 10.1016/j.biomaterials.2018.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Controlled M1-to-M2 transition of aged macrophages by calcium phosphate coatings

Abstract: Older adults suffer from weakened and delayed bone healing due to age-related alterations in bone cells and in the immune system. Given the interaction between the immune system and skeletal cells, therapies that address deficiencies in both the skeletal and the immune system are required to effectively treat bone injuries of older patients. The sequence of macrophage activation observed in healthy tissue repair involves a transition from a pro-inflammatory state followed by a pro-reparative state. In older pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 85 publications
2
56
0
Order By: Relevance
“…A biomimetic calcium phosphate (bCaP) coating layer was designed to cover and separated the pro-M2 molecule simvastatin (SIMV) from IFN-γ to delay the stimulation of pro-reparative state following a pro-inflammatory phenotype ( Fig. 3 D) [ 136 ]. The successive M1 to M2 activation on this dual drug delivery system was observed with both THP-1 and bone marrow macrophages ( Fig.…”
Section: Harnessing the Power Of Macrophages For Enhanced Osteogenesimentioning
confidence: 99%
See 1 more Smart Citation
“…A biomimetic calcium phosphate (bCaP) coating layer was designed to cover and separated the pro-M2 molecule simvastatin (SIMV) from IFN-γ to delay the stimulation of pro-reparative state following a pro-inflammatory phenotype ( Fig. 3 D) [ 136 ]. The successive M1 to M2 activation on this dual drug delivery system was observed with both THP-1 and bone marrow macrophages ( Fig.…”
Section: Harnessing the Power Of Macrophages For Enhanced Osteogenesimentioning
confidence: 99%
“…Reprinted with permission from Ref. [ 73 , 135 , 136 ], Copyright (2014) Elsevier, Copyright (2018) Wiley and Copyright (2018) Elsevier. …”
Section: Harnessing the Power Of Macrophages For Enhanced Osteogenesimentioning
confidence: 99%
“…The results could be correlated with the ability of Lf to modulate the polarization of macrophages through its anti-inflammatory properties [82] and also with the hydrophilic character of the hybrid coating [14]. In addition, M1-to-M2 transition on hybrid coatings of THP-1 cells stimulated with LPS could also be explained by the interference of the hydroxyapatite component [99,100] and the polymeric coating, which might be involved in a controlled release of the anti-inflammatory component [58].…”
Section: Surface Effect On Macrophage Polarizationmentioning
confidence: 77%
“…For example, it has been reported that calcium and strontium ions on a nanostructure titanium surface can increase M2 macrophage phenotype (Lee, Kim, Jang, & Park, 2016) or hydroxyapatite granules activate some M1, but more M2 activation of THP-1 cells (Fernandes, Zhang, Magri, Renno, & Van Den Beucken, 2017). Another study reported that carbonated hydroxyapatite in the form of a coating rather than in granules was a potent M1 stimulator for THP-1 cells, and then transitioned to M2 via simvastatin delivery (Alhamdi et al, 2018). In the present studies, we demonstrated that DDSA-collagen gels and materials carrying simvastatin were modulators of an M2 profile for THP-1 cells.…”
Section: Discussionmentioning
confidence: 99%